The Impact of Implementing an Information Technology-Based Accounting System on Operational Efficiency at PT Bank Bjb (Persero) KCP Cicurug - Lalita Nafilah; Dania Meida Rosyidah (Edumedia Solution, 2026)
This study examines how PT Bank BJB KCP Cicurug operational efficiency is affected by the use of an IT-based accounting system. Between January and June of 2025, the study employed a qualitative methodology and collected data via observation, semi-structured interviews, and documentation studies. The outcomes demonstrate that the Core Banking System (CBS) implementation and e-channel has improved operational efficiency through accelerated transaction processes, increased data accuracy, and reduced manual errors. However, major obstacles were found in the form of IT infrastructure disruptions, gaps in customer digital literacy, and dependence on manual processes for certain transactions. The proposed solutions include the implementation of ISP backup, the development of an offline mode system, human resource training, and a customer digital education program. This study provides practical contributions in the form of recommendations for improving IT-based accounting systems in regional banks.